Qur’anic Narrative Learning Model (QNLM): An Innovative Synthesis of Qur’anic Narrative-Based Learning and Student-Centered Learning - Susetyo, Marwal Blantara; Syahidin, Syahidin (Universitas Muhammadiyah Yogyakarta, 2026)
This study aims to propose a formulation of instructional steps for the Quranic Narrative Learning Model (QNLM), combining the pedagogical advantages of Quranic narratives with a variety of Student-Centered Learning (SCL) approaches to facilitate students' tazkiyatun nafs (self-acceptance). The development of this model addresses the persistent problem faced by Islamic Religious Education (IRE): a focus on cognitive achievement that often neglects the affective aspect, due to a situational process caused by the dominance of teacher-centered learning. Using a qualitative conceptual design, this study adopted a Comparative-Synthetic Analysis. The literature was rigorously and systematically reviewed through three phases: conceptual analysis of SCL and Quranic pedagogy, comparative integration, and model development. The findings outline a learning syntax with five main stages: Preparation & Hook, Inquiry Analysis, Value Connection, Reinforcement, and Implementation & Evaluation. The main novelty of QNLM lies in the setting time technique; This approach shifts the narrative's chronological order to immediately engage students emotionally and aims to control the lesson ('ibrah) in a delayed manner to ensure deeper affective internalization. This systematic approach effectively addresses the risk of a lack of religious and ethical foundations within the SCL environment. Consequently, the QNLM provides a practical, structured system for values-based learning in modern IRE. Future empirical studies are expected to incorporate classroom action research or comparative studies to validate this model's capacity to shape long-term changes in student behavior.